2015
DOI: 10.1515/jpem-2014-0444
|View full text |Cite
|
Sign up to set email alerts
|

17α-Hydroylase/17,20-lyase deficiency related to P.Y27*(c.81C>A) mutation in CYP17A1 gene

Abstract: 17α-Hydroxylase/17-20 lyase deficiency (17OHD) is a rare form of congenital adrenal hyperplasia. Genetic defects causing combined 17OHD lead to the impaired production of cortisol and sex steroids, accumulation of mineralocorticoids, and compensatory overproduction of pituitary adrenocorticotropic hormone. Consequently, individuals with this enzymatic defect present with both adrenal cortical hyperplasia and variable degrees of hypertension, hypokalemia, and sexual immaturity. The patient was aged 15 years and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…CYP17A1 gene mutations associated with 17-OHD previously reported from Turkey are: large deletions exons 1-6 (eight patients from two different families) (11,12), stop codon mutation p.Y27*(c.81C>A) in exon 1 (two patients from different families) (13,14), R239Q(G>A) exon not-known (one patient) (15), and a point mutation c.1307G>A (one patient) (16). …”
Section: Discussionmentioning
confidence: 99%
“…CYP17A1 gene mutations associated with 17-OHD previously reported from Turkey are: large deletions exons 1-6 (eight patients from two different families) (11,12), stop codon mutation p.Y27*(c.81C>A) in exon 1 (two patients from different families) (13,14), R239Q(G>A) exon not-known (one patient) (15), and a point mutation c.1307G>A (one patient) (16). …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, protein structure analysis has been done to examine the impact of specific mutants on a form of CAH known as salt-water wasting disease, which if left undiagnosed leads to low sodium levels and death (Haider et al, 2013). CYP17A1 is heavily involved in steroidogenesis, with deletion mutations leading to hormone production inhibition and sex development abnormalities (Keskin et al, 2015;Turkkahraman et al, 2015;Zhang et al, 2015;Papi et al, 2018;Xia et al, 2021). Recent genome studies of 17OHD patients revealed 46,XY karyotype in physically presenting females which cooccur with multiple mutations in the CYP17A1 gene (Zhang et al, 2015;Xia et al, 2021).…”
Section: Investigation Of Outlier Genes Associated With Genital Morphologymentioning
confidence: 99%
“…Additionally, protein structure analysis has been done to examine the impact of specific mutants on a form of CAH known as the salt‐water wasting disease, which if left undiagnosed leads to low sodium levels and death (Haider et al, 2013 ). CYP17A1 is heavily involved in steroidogenesis, with deletion mutations leading to hormone production inhibition and sex development abnormalities (Keskin et al, 2015 ; Papi et al, 2018 ; Turkkahraman et al, 2015 ; Xia et al, 2021 ; Zhang et al, 2015 ). Recent genome studies of 17OHD patients revealed 46,XY karyotypes in physically presenting females which co‐occur with multiple mutations in the CYP17A1 gene (Xia et al, 2021 ; Zhang et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%